Combining data from consumers and traditional medicine practitioners to provide a more complete picture of Chinese bear bile markets - Hinsley, A; Hu, S; Chen, H; Garshelis, D; Hoffmann, M; Lee, TM; Moyle, B; Qiu, Y; Ruan, X; Zhou, J; Milner-Gulland, E (Wiley, 2021)
1. Understanding wildlife consumption is essential for the design and evaluation of effective conservation interventions to reduce illegal trade. This requires understanding both the consumers themselves and those who influence their behaviour. For example, in markets for wildlife-based medicines, both consumers and medical practitioners have a role in which products are consumed. 2. We used mixed methods to triangulate data on bear bile consumption from 3646 members of the public, 80 pharmacy workers and 38 Traditional Chinese Medicine (TCM) doctors in four provincial capital cities across China. Bear bile can be sold legally in packaged TCM products made from farmed bile, or sold illegally, often as raw gallbladders from wild bears. We interviewed medical practitioners, and surveyed the public using both direct questions (DQ) and the Unmatched Count Technique (UCT), an indirect method used to improve reporting of sensitive behaviours. We applied a ‘combined’ UCT-DQ analysis, to produce a more robust consumption estimate. 3. One-hundred-and-forty (3.8%) survey respondents directly reported recent (<3 years) bile consumption, but the combined UCT-DQ estimate was 11.2%. Fourteen survey respondents (0.4% sample, 10% recent consumers) self-reported recent wild bile consumption. Almost a quarter of doctors and half of pharmacy workers had ever prescribed bile. 4. Around half of doctors and over a quarter of pharmacy workers said that bear bile was the best medicine in certain situations. More than half of doctors and over a third of pharmacy workers thought wild bile was more effective than farmed, although we found no evidence of wild bile being formally prescribed. Consumers could name specific treatment-uses of bile but almost half of recent consumers did not know the source of bile they had consumed. 5. We show that gathering perspectives from different wildlife market actors can generate a more complete picture of trade. In China, bile consumption may be limited by its specific TCM treatment-uses, but whether practitioner views on the greater effectiveness of wild bile are passed to consumers must be investigated further. With potential overlap between farmed and wild consumption, any interventions to change these markets must carefully consider how both consumers and practitioners may react.